Estrogen transcriptomic regulation of brain bioenergetics and metabolism is cell‐type‐specific and estrogen‐receptor‐subtype‐dependent. (December 2021) - Wang, Yiwei; Shang, Yuan; Yin, Fei; Brinton, Roberta Diaz
Abstract: Background: Late onset AD has an approximately 20‐year prodromal period, which is characterized by brain glucose hypometabolism that can be detected in at risk groups and is predictive of disease progression. In females, this prodromal period coincides with the perimenopausal transition, during which loss of ovarian hormones is also associated with brain glucose hypometabolism. Further, in postmenopausal women, estrogen replacement therapy has demonstrated efficacy in improving brain glucose metabolism and recognition, supporting the role of estrogen (E2) as a master regulator of brain bioenergetics. Our previous studies demonstrated that in neurons, estrogen receptor beta (ERβ), not estrogen receptor alpha (ERα), co‐localizes with mitochondria, and has a functional role in ATP production, indicating a cell type and ER subtype dependent regulation of brain bioenergetics. In this study, we investigated the differential transcriptomic response of key nodes involved in metabolism, nuclear‐mitochondrial integration, energy sensing and redox sensing to E2 treatment. Method: To identify cell type‐specific responses to estrogen treatment, rat embryonic primary neurons and enriched astrocytes were treated with 10nM E2 for 24 hours. To identify the contribution of ER subtypes, cells were treated with either ERα selective antagonist (MPP), or ERβ selective antagonist (PHTPP) prior to E2 treatment. Gene expression profiles for key regulators were determined by RNA‐Seq. Result: Estrogen transcriptomic regulation of bioenergetics and metabolism, PI3K and AKT signaling, substrate transport, and redox sensing was evident in both cell types, with a stronger effect in neurons than in astrocytes. Estrogen transcriptomic regulation of key metabolic enzymes are further ER subtype specific. In neurons, both ERα and ERβ inhibition led to disruption of TCA cycle and activation of fatty acid and cholesterol metabolism compared to unopposed E2 treatment, whereas in astrocytes, ERα inhibition tended to activate ketone body metabolism while ERβ inhibition tended to activate fatty acid and cholesterol metabolism. Conclusion: Our analyses indicated that estrogen regulation of metabolism, nuclear‐mitochondrial integration, energy sensing and redox sensing is cell type specific, with an overall stronger impact in neurons than in astrocytes. Further, neuronal vs astrocytic dependent responses to estrogen are ER subtype specific.